THE IMPACT OF WORKLOAD AND WORK STRESS ON EMPLOYEE PERFORMANCE: A JOB DEMAND – RESOURCES THEORY PERSPECTIVE - Lusia Adinda Dua Nurak; Maria Yubiliani Laetare Nurak; Vera Herlina Mustari; Agustinus Lado Brewon (CV. Adiba Aisha Amira, 2025)
Testing the Job Demands–Resources (JD-R) theory, this study aims to analyze the effect of workload on employee performance with job stress as a mediating variable. The research sample consists of 35 employees in the Nogo ikat weaving industry in Sanur, Bali. Data were collected through a questionnaire using a 5-point Likert scale, and analyzed using the SEM-PLS method with the help of Warp-PLS version 7 software. The results show that workload has a significant negative effect on employee performance, both directly and indirectly through job stress. Job stress is proven to act as a partial mediator in this relationship. The findings highlight the importance of effective workload and stress management as a strategy to maintain employee performance in traditional, high-demand work environments.